Penggunaan Problem Based Learning untuk Meningkatkan Kemampuan Berpikir Kreatif dalam Pembelajaran Biologi Siswa Kelas VII di Salah Satu SMP Negeri di Surakarta - Sutanto, Wiji; Marjono, Marjono; Ramli, Murni (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2018)
This research was aimed to improve the student’s creative thinking skill in VII F of SMP Negeri 8 Surakarta academic years 2014/2015 about biology lesson through problem based learning application.This research was a class action research which consisted of three cycles. Each cycle contains planning, implementing, observing and reflecting. The research subject was the 30 students of VII F of SMP N 8 Surakarta Academic Year 2014/2015. Data collecting techniques of this research used testing, observation, and interview then data validation was using triangulation method. Data analyzing technique of this research was descriptive qualitative analysis which was done in three components, they are: data reduction, data presentation and drawing the conclusion or verification. The research’ procedure used spiral mode which is interdependent.The research’s result showed that the implementation of problem based learning improves the student’s creative thinking skill that covers aspects of fluency, flexibility, originality,danelaboration. The percentages of fluency aspect was 45,00% in pre cycle, 51,79% in first cycle, 59,17% in second cycle, and 73,33% in third cycle. The percentages of flexibility was 31,67% in pre cycle, 33,93% in first cycle, 44,17% in second cycle, and 56,67% in third cycle. The percentages of originality aspect was 18,33% in pre cycle, 24,11% in first cycle, 30,00% in second cycle, and 39,17% in third cycle. The percentages of elaboration aspect was 35,00% in pre cycle, 41,96% in first cycle, 50,00% in second cycle, and 55,83% in third cycle.This research’s conclusion was the implementation of problem based learning can improve the student’s creative thinking skill in VII F of SMP N 8 Surakarta academic year 2014/2015 about biology lesson.